Building Life Skill and Enterpreneurship Educational Skill Through Project Based Learning in Urban Farming Courses - Hasminar Rachman Fidiastuti; Nila Kartika Sari (Jurnal Biologi Tropis, 2022)
Urban farming is one of the elective courses that characterize the Biology Education study program, Tribhuwana Tunggadewi University. This course has learning outcomes so that students have the ability to determine and reflect on themselves about the important value of urban farming, through its application to the preservation of the urban environment, as part of life skills. The purpose of this study was to identify life skills and entrepreneurship skills in students participating in the Urban Farming course at Biology Education Study Program, Tribhuwana Tunggadewi University through project-based learning. The data in this study are test results (pretest and posttest), tested using One Group Pretest-Posttest Design. The data is also equipped with a questionnaire as a result of student reflection. The gender distribution of survey respondents in the Urban Farming course is 45% (9 people) male students and 55% (11 people) female students. Based on the median value of 12.50 at the pretest and 18.00 at the post-test, it shows that there is an increase in life skill scores before and after the implementation of project based learning. Entrepreneurship Educational Skill scores are based on a median value of 14.00 at the pretest and 18.00 at the posttest. This shows that there is an increase in the score of Entrepreneurship Educational Skills before and after the implementation of project based learning. Through the entrepreneurial project "urban farming" students form life skills in the future and have entrepreneurial educational skills that have potential for the future.